298, -70, 114, 22, 68, 45
Let's start with our initial sequence.
a, b, c, 22, e, 45
Since the average of 22 and e is equal to 45, we have
(22 + e)/2 = 45
22 + e = 90
e = 68
So our sequence is now
a, b, c, 22, 68, 45
And since 68 is the average of c and 22, we have
68 = (c + 22)/2
136 = c + 22
114 = c
So our sequence is now
a, b, 114, 22, 68, 45
And b becomes
22 = (b + 114)/2
44 = b + 114
-70 = b
So our sequence is now
a, -70, 114, 22, 68, 45
And finally, for a, we have
114 = (-70 + a)/2
228 = -70 + a
298 = a
So the final sequence becomes
298, -70, 114, 22, 68, 45